Additive manufacturing - welding composite repair of Q235 steel: interface microstructure control - Fengya Hu; Yang Yu; Tie Liu; Guorui Sun; Chao Chen (Journal of Materials Research and Technology)
Heterogeneous material welding technology has been widely applied in various industrial production processes. However, research on utilizing heterogeneous material welding processes for part repair and processing remains scarce. This study aims to combine part additive manufacturing repair technology with dissimilar material joining technology, using additive manufacturing of 304 stainless steel to repair notches in Q235 carbon steel parts, and employing the GTAW process to weld the two materials together. The study also investigates the effects of different arc offset positions on the microstructure and corrosion performance of the welded joints in the repair zone, as well as the underlying mechanisms. The research results indicate: coarse-grained zones and fine-grained zones were observed in the heat-affected zone on the Q235 steel side of each sample, while no obvious heat-affected zone was found on the 304 stainless steel additive manufacturing side; when the arc is biased toward the Q235 steel, the plate-like martensite has larger dimensions and stronger orientation; When the arc is shifted to AM 304 stainless steel, the weld exhibits significantly better corrosion resistance (Jcorr = 2.158 × 10−6 A/cm2) than the weld with the arc shifted to the Q235 side (Jcorr = 4.571 × 10−6 A/cm2), with the corrosion rate increasing by more than double.